2021
DOI: 10.1080/00016489.2021.1921843
|View full text |Cite
|
Sign up to set email alerts
|

Adults with unilateral congenital ear canal atresia – sound localization ability and recognition of speech in competing speech in unaided condition

Abstract: Background: Individuals with unilateral hearing loss show poor spatial hearing, but individual variability is high. Aims/objectives: To investigate if the degree of hearing loss in unilateral ear canal atresia affects horizontal sound localization and speech recognition. Materials and methods: Twelve subjects with unilateral ear canal atresia without childhood hearing intervention. Previously published data from eight normal-hearing subjects in normal binaural as well as experimentally induced unilateral heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Although a thinner cortex of the left than the right HG in UCA was observed, the thickness of the left HG was not associated with PTA. The present study did not present speech perception data, although speech discrimination in noise is worse in unilateral atresia than in NH (5,38). Together, this may indicate that the level of hearing loss is not the primary problem, but rather the central processing of more complex sounds.…”
Section: E346contrasting
confidence: 71%
“…Although a thinner cortex of the left than the right HG in UCA was observed, the thickness of the left HG was not associated with PTA. The present study did not present speech perception data, although speech discrimination in noise is worse in unilateral atresia than in NH (5,38). Together, this may indicate that the level of hearing loss is not the primary problem, but rather the central processing of more complex sounds.…”
Section: E346contrasting
confidence: 71%
“…For cochlear implant subjects, a bilateral advantage was demonstrated in speech recognition in a complex noisy environment ( Mosnier et al, 2009 ). Moreover, individuals with congenital unilateral ear canal atresia show impaired speech recognition in the presence of competing speech ( Siegbahn et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The speech discrimination is better binaurally than monaurally under reverberation for both normally hearing and hearing-impaired subjects ( Gelfand and Hochberg, 1976 ). Besides, unilateral hearing loss impairs the recognition of speech in competing speech ( Siegbahn et al, 2021 ), and the adult patients with bilateral cochlear implants demonstrated a bilateral advantage for speech perception in bilateral listening mode compared to unilateral listening mode in both quiet and noisy environments ( Litovsky et al, 2006 ; Mosnier et al, 2009 ). Speech perception in noise is shown to be improved after corrected congenital unilateral conductive hearing loss ( Wilmington et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…In unilateral atresia, significant benefits of hearing rehabilitation include the ability to localize sound and understand speech in the presence of background noise. [8][9][10][11] Rehabilitation of hearing loss due to congenital aural atresia or a closed ear canal is challenging due to the unique anatomic constraints that preclude use of a traditional air conduction hearing aid. Trends over time have shown a shift away from atresiaplasty surgery and toward BCD implants, which typically provide more reliable hearing results with lower surgical risks.…”
Section: Discussionmentioning
confidence: 99%
“…In bilateral atresia, hearing rehabilitation is necessary to enable auditory‐verbal communication. In unilateral atresia, significant benefits of hearing rehabilitation include the ability to localize sound and understand speech in the presence of background noise 8–11 . Rehabilitation of hearing loss due to congenital aural atresia or a closed ear canal is challenging due to the unique anatomic constraints that preclude use of a traditional air conduction hearing aid.…”
Section: Discussionmentioning
confidence: 99%